Peach leaf physiology and irrigation water and light availability - Pliakoni E.; Kalorizou H.; Nanos G.D. (Irrigation in Mediterranean agriculture: challenges and innovation for the next decades, 2008)
We studied the effect of available water and light into the canopy on leaf characteristics and physiology of two clingstone peach cvs. Irrigation water was reduced by 90 percent (deficit) since late June (3 weeks before harvest) and, the same day, 1.2 m wide Extenday reflective mulch strip was applied on the row. Incident and reflected ultraviolet (UV) and photosynthetically active radiation (PAR) were measured inside the canopy. Specific leaf weight (SLW) and chlorophyll content were measured every month from late May to late August on light exposed and shade leaves. Photosynthesis (Ps), transpiration (E) and other physiological parameters were measured or calculated in light exposed leaves periodically. The reflective mulch significantly increased reflected UV and PAR radiation in the canopy compared to control, while no similar trend was found for incident radiation. SLW and chlorophylls (a, b and total) were not affected by treatment in both cvs, while significant changes with time and leaf position were always observed. Deficit irrigation increased leaf temperature and decreased stomatal conductance, Ps and water use efficiency (WUE) compared to control. Combination of reflective mulch and water deficit was even more detrimental to leaf physiological functions as this combination treatment increased leaf temperature and decreased E, stomatal conductance, Ps, WUE and quantum yield compared to control and often to other treatments.
International Conference on Irrigation in Mediterranean Agriculture: Challenges and Innovation for the Next Decades, 2008/06/17-18, Naples (Italy)